When a Massage Gone Wrong: Unveiling a Case of Post-Massage Brachial Plexopathy - Anggi Gilang, Yudiansyah; Noor, Syeda Tazkia; Lestari, Dwi Indriani; Pringga, Gutama Arya (Faculty of Medicine, Universitas Airlangga, 2025)
The brachial plexopathy associated with massage therapy is rarely reported. This case report describes an uncommon case of brachial plexopathy that developed after a session of massage therapy and revealed past published reports of peripheral nerve injury following massage therapy. A 54-year-old Javanese woman developed sudden unilateral paralysis of her left shoulder girdle after a session of massage therapy. The massage session was stopped due to pain. She could not move her left shoulder immediately after 5 minutes of massage. There was hypoesthesia from shoulder to forearm, and there was decreased MMT of the left deltoid muscle. She regularly participated in a twice-weekly rehabilitation program targeting the left shoulder. It included NMES, laser therapy, PROM, strengthening exercises, and a home exercise program. A diagnosis of acute brachial plexopathy was suspected due to her recent history and the results of several examinations. She had a gradual recovery of strength, resolution of limitations of ROM, and sensory function in her shoulder. Rehabilitation programs have a major role in helping the patient do her functional activities. This case report presents as a reminder to massage therapists or physical therapists that massage therapy of the neck and shoulder should be carefully performed to avoid any injury. Further studies will help improve the safety procedures and effectiveness of massage therapy in the future.